Depressed demand for crop insurance contracts, and a rationale based on third generation Prospect Theory. (14th November 2019) - Feng, Hongli; Du, Xiaodong; Hennessy, David A.
Abstract: When actuarially fair insurance for a major risk is available then standard economic theory posits that those subject to the risk should insure. In agriculture, it is common for producers to decline contract offers where presubsidy premiums just cover average losses and subsidies are substantial. This paper seeks to shed light on why demand is curtailed. In a mail survey of U.S. corn and soybean producers we solicited Willingness to Pay (WTP) for actuarially fair insurance at different coverage levels. We find demand to be so low that median WTP is no larger than fair premium when adjusted down by current subsidy rates, which pay for one half or more of most premium charges. WTP as a share of the fair rate is especially low when risk of loss is high. There is limited evidence that respondents appreciate the convex relationship between coverage level and expected indemnity payoff. Third generation Prospect Theory is shown to be consistent with observed findings. In particular, a strong distaste for paying premium can be rationalized by loss aversion. Furthermore, when high revenue outcomes are more likely than not, that is, negative skewness, then higher loss aversion, greater decision weight distortions and greater risk aversion will decrease WTP.